Thermal and energy performance of innovative prismatic building forms - Adinugroho, Teguh P. (2021)
Already built prismatic buildings show that such forms have an appealing look and past studies have proven that it helps to save energy. Segmentation and inclination are two features exist in prismatic building forms, but the impact from each of them are not yet fully understand, since past studies were more centered to downward inclined wall – also known as self-shading – or just studied one sample of prismatic building as a whole. Thus, a study using diverse prismatic forms tested in different conditions is needed to fill the gap about providing a fundamental understanding to architects regarding the impact of segmentation and inclination to thermal and energy performance. Insights from the use of segmentation and inclination associated with thermal and energy saving performance are expected to help green building project since the early design stage, even before the energy simulation, and to diminish greenhouse gases.